Attitudes towards Donor Breast Milk in an Inner City Population. (1st January 2019) - Pal, Abhinav; Soontarapornchai, Kultida; Noble, Lawrence; Hand, Ivan
Abstract : Objective. The purpose of our study was to identify attitudes towards donor breast milk in our population and identify barriers to its acceptance. Methods. The study sample was comprised of a convenience sample of 174 postpartum women. A questionnaire consisting of demographic information and 12 questions relating to attitudes and understanding of donor breast milk was administered. Results. Among the mothers surveyed, 34% were aware of the use of donor breast milk and donor milk banks. 62% of mothers preferred the use of formula compared to donor breast milk if they were unable to provide their own breast milk. Educational level did play a role with 64% of mothers with education beyond high school believing that donor breast milk was beneficial for newborns as opposed to 46% with a high school education or less (p=0.02). US born mothers were more likely to have heard about donor breast milk (47% versus 29%, p=0.025) than foreign born mothers although they were less likely to believe it was a better option for feeding than formula (22.7% versus 43%, p=.016). Mothers with infants in the NICU were more likely than mothers of well babies to accept milk from a milk bank rather than a relative or friend (81% versus 39%, p≤0.001). Conclusion . Although the beneficial effects of donor breast milk are well established in the scientific community, there remains a lack of awareness and a major discrepancy in the understanding and acceptance of it within our community. Education on the benefits of mother's own milk as well as donor breast milk and milk banks is an important public health initiative needed to increase acceptance of human milk as the optimal form of nutrition in infants.